Barriers to Integrating Tobacco Dependence Treatment into Lung Cancer Screening: A Qualitative Assessment - Deborah L. Pestka; Megan E. Campbell; Naomi A. Schmulewitz; Anne C. Melzer (Journal of Primary Care & Community Health)
Introduction/objective: We qualitatively assessed current practices and perceived barriers surrounding the integration of tobacco dependence treatment (TDT) into lung cancer screening (LCS). Methods: Informed by the Practical, Robust Implementation and Sustainability Model, we conducted semi-structured interviews with clinicians ( n  = 18) at 6 Veterans Affairs medical centers in the Midwest. Results: TDT was usually addressed at an initial shared decision-making visit but often not with subsequent rounds of screening or nodule follow-up. No site was aware that any TDT-related outcomes were tracked within their program. While the LCS clinical reminders included some aspects of tobacco use (eg, tobacco pack-years), they did not support clinicians in offering TDT or capture outcomes and were perceived as “checkboxes to nowhere.” This was contrasted with other clinical reminders linked to dashboards that provide rolling feedback for important clinical outcomes (eg, diabetes care). Interviewees reported competing demands and limited expertise in motivational interventions as additional barriers. A dedicated team for TDT and a “one-click referral” were perceived as key success factors. Conclusions: TDT remains poorly integrated into LCS. Addressing identified barriers will require considerable investment in TDT resources and improvements to LCS tools to support the provision of cessation support.